Improvement in left ventricular mechanics following medical treatment of constrictive pericarditis. Issue 10 (6th January 2021) - Sato, Kimi; Ayache, Ayman; Kumar, Arnav; Cremer, Paul C; Griffin, Brian; Popovic, Zoran B; Jellis, Christine; Kwon, Deborah H; Bolen, Michael; Ramchand, Jay; Chetrit, Michael; Furqan, Muhammad M; et al.
Abstract : Objective: Patients with constrictive pericarditis (CP) with active inflammation may show resolution with anti-inflammatory therapy. We aimed to investigate the impact of anti-inflammatory medications on constrictive pathophysiology using echocardiography in patients with CP. Methods: We identified 35 patients with CP who were treated with anti-inflammatory medications (colchicine, prednisone, non-steroidal anti-inflammatory drugs) after diagnosis of CP (mean age 58±13; 80% male). Clinical resolution of CP (transient CP) was defined as improvement in New York Heart Association class during follow-up. We assessed constrictive pathophysiology using regional myocardial mechanics by the ratio of peak early diastolic tissue velocity (e') at the lateral and septal mitral annulus by tissue Doppler imaging (lateral/septal e') or the ratio of the left ventricular lateral and septal wall longitudinal strain (LSlateral /LSseptal ) by two-dimensional speckle-tracking echocardiography. Longitudinal data were analysed using a mixed effects model. Results: During a median follow-up of 323 days, 20 patients had transient CP, whereas 15 patients had persistent CP. Transient CP had higher baseline erythrocyte sedimentation rates (ESR) (p=0.003) compared with persistent CP. There were no significant differences in LSlateral /LSseptal and lateral/septal e'. During follow-up, only transient CP showed improvement in lateral/septal e' (p<0.001) and LSlateral /LSseptal (p=0.003), and recovery of inflammatory markers was similar between the two groups. In the logistic model, higher baseline ESR and greater improvement in lateral/septal e' and LSlateral /LSseptal were associated with clinical resolution of CP using anti-inflammatory therapy. Conclusions: Improvement of constrictive physiology detected by lateral/septal e' and LSlateral /LSseptal was associated with resolution of clinical symptoms after anti-inflammatory treatment. Serial monitoring of these markers could be used to identify transient CP.